OPTIMALISASI PERAN GURU DALAM PENINGKATAN KEGIATAN BELAJAR PESERTA DIDIK DI MTS. MADANI ALAUDDIN PAOPAO KABUPATEN GOWA - Saprin, Saprin (Universitas Islam Negeri Alauddin Makassar, 2016)
This research was positivistic aiming to answer the research problem, namely: 1) how is the realization of the teachers’ role in the learning process; 2) how are the learning activities of students; and 3) can the optimization of the teachers’ role improve students’ learning activities that have been implemented in MTs. Madani Alauddin Paopao Gowa. Then, the samples of this study were 20 teachers and 20 students chosen proportionately 15% of 284 students as the population with stratified random sampling technique. The data were collected by using questionnaires, observation sheets, and format documents. Then, they were analyzed using descriptive statistics. Further, hypothesis testing concluded that; 1) the average score of optimization of the teachers’ role was about 62.6: 20 = 3:13 categorized frequently - so, the teachers often optimize their role as a source of learning, facilitator, manager, demonstrator, mentor, motivator, and evaluator in the learning process at MTs Madani Alauddin Paopao Gowa; 2) the average score of students’ learning activities was about 56 467: 20 = 2.82 categorized often – so the learners often do learning activities in the form of observing, asking, gathering information, associating/processing information, and communicating in the learning process at MTs. Madani Alauddin Paopao Gowa; and 3) the score improvement in the students’ activities into 42.1524 if the score of optimizing the teachers’ role increased being 56. It means that in order to increase the students’ learning activities increased 1 then the mean score of optimization the teachers’ role in teaching should be increased into 56: 42.1524 = 1.33. In accordance with the conclusions and hypothesis testing, it was found that: 1) the teachers’ role in MTs. Madani Alauddin Paopao Gowa can be implemented in the learning process because the results are positive; 2) the students’ learning activities in MTs. Madani Alauddin Paopao Gowa can be improved in the learning process because the results are also positive; and 3) the learners’ activities can be increased through optimizing the teachers’ role in the learning process in MTs. Madani Alauddin Paopao Gowa because the results were influencing.